Adhesion of Enteroaggregative E. coli Strains to HEK293 Cells - Jorge Ayala-Lujan; Fernando Ruiz-Perez (Bio-Protocol, 2018)
Enteroaggregative Escherichia coli (EAEC) is a recognized cause of acute diarrhea among both children and adults worldwide. EAEC strains are characterized by the presence of aggregative adherence fimbriae (AAF), which play a key role in pathogenesis by mediating attachment to the intestinal mucosa and by triggering host inflammatory responses. The aggregative adherence fimbria II (AAF/II) is the most important adherence factor of EAEC prototype strain 042 (EAEC042) to intestinal cells. Multiple receptors for AAF/II on epithelial cells have been identified including the transmembrane signaling mucin Muc1. This protocol describes a method to measure adherence of EAEC strains to HEK293 cells expressing the Muc1 glycoprotein.